VILLAGE ADMINISTRATORS’ QUALITY OF WORK: EVALUATION AND IMPROVEMENT - Nisha Faradilla Sofiani; Metha Djuwita Supriatna (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Cisondari Village is responsible for village administration as well as providing services to the local village community in Pasirjambu District, Bandung Regency. In practise, however, there are several issues that concern village administrators. Based on initial observations and interviews, the village administrators were still deemed ineffective in carrying out their duties. The goal of this research is to identify the root cause of a problem related to the effectiveness of village administrators' work in Cisondari Village and to propose solutions. To identify the source of a problem, a fishbone diagram is used, and the Five Whys method was used to collect the necessary information through interviews. Based on the analysis, it was discovered that the understanding of the main tasks and functions, as well as the still diverse work procedures, play an important role in the problem of the effectiveness of village administrators' work, as well as a lack of discipline in working. Some of the solutions that can be provided include designing the Disciplinary Standard Operational Procedure document, compiling a job analysis document and workload analysis, and compiling a Village Administrators Performance Monitoring System.